Antifungal and antiaflatoxigenic effects of a fumigant, ethanedinitrile, on Aspergillus flavus - Choi, Hoon; Lee, Byung-Ho; Moon, Young-Sun; Kim, Kyeongsoon; Lee, Hoi-Seon; Lee, Sung-Eun (Applied biological chemistry, 2017)
Antifungal effects of ethanedinitrile (EDN) and ethyl formate (EF) on Aspergillus flavus were investigated using radial growth bioassay. A. flavus was inoculated in the center of potato dextrose agar plate and treated with 1, 5, and 10 g/m 3 of EDN, or 5, 35, and 70 g/m 3 of EF. EDN strongly inhibited fungal growth. At 1 g/m 3 of EDN, the fungal growth reduced by 22.2% by the final days of culture. The growth was completely inhibited by EDN at the concentration of 5 g/m 3 . Antiaflatoxigenic activity of both the fumigants was also assessed. Aflatoxin formation was determined using high-performance liquid chromatography with a fluorescence detector. A. flavus did not produce aflatoxin B 1 and aflatoxin B 2 at EDN concentrations >5 g. EF had no inhibitory effect on A. flavus growth and the formation of aflatoxin. These results suggest that EDN can be an alternative for currently used antifungal agents to control fungal and aflatoxin contamination of stored grains.